The Impact of Job Satisfaction, Welfare, and Visionary Leadership on Employee Organizational Commitment at Teuku Umar Aceh Jaya Regional General Hospital - Salawati; Sidauruk, Risma Agustina; Ritonga, Irsyad Praja Fahmi; Ritonga, Zulfadly Alhabsyi; Fahmi, Ahmad; Nasti, Nilawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the impact of job satisfaction, welfare, and visionary leadership on employee organizational commitment at the Teuku Umar Aceh Jaya Regional General Hospital (RSUD). Organizational commitment is a key factor in improving individual and institutional performance, especially in the health service sector. Employee job satisfaction and well-being play an important role in creating a supportive work environment, while visionary leadership can provide strategic direction that motivates employees to achieve organizational goals. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to 100 employees of Teuku Umar Hospital, which was selected using a stratification sampling technique. Data analysis was carried out using multiple regression to test the influence of each independent variable on the dependent variable. The results of the study show that job satisfaction, welfare, and visionary leadership have a significant effect simultaneously or partially on employee organizational commitment. Visionary leadership has the greatest influence, followed by job satisfaction and well-being. These findings underscore the importance of leadership that inspires a shared vision and the need to improve job satisfaction and well-being to strengthen employee commitment to the organization. The recommendations of this research include the development of visionary leadership training programs, improvement of work facilities, and the preparation of welfare policies oriented to employee needs. This research contributes to understanding the factors that affect organizational commitment in the health service sector and can be a reference for policymakers in an effort to improve the quality of hospital services.